Cortical folding in post‐traumatic stress disorder after motor vehicle accidents: Regional differences in gyrification. Issue 4 (7th February 2017) - Chu, Chun; Xie, Bing; Qiu, Mingguo; Liu, Kaijun; Tan, Liwen; Wu, Yi; Chen, Wei; Zhang, Shaoxiang
Abstract : Aim: Structural and functional magnetic resonance imaging (MRI) studies have revealed evidence of brain abnormalities in post‐traumatic stress disorder (PTSD) patients. Cortical complexity and local gyrification index (lGI) reflect potential biological processes associated with normal or abnormal cognitive functioning. In the current study, lGI was used to explore cortical folding in PTSD patients involved in motor vehicle accidents (MVA). Methods: MRI brain scans were acquired from 18 PTSD patients who had suffered MVA at least 6 months previously and 18 healthy control subjects. All MRI images were obtained on a 3‐T Siemens MRI machine and the cortical folding was analyzed using the workflow provided by softwareFreeSurfer . A generalFreeSurfer 's general linear model was used in the group analysis. In addition, correlation analysis was performed between the average of lGI extracted from the significantly different areas and the data for the clinical scale. Results: The PTSD patients had significantly greater Clinician‐Administered PTSD Scale scores than the control group. The patients showed significantly reduced lGI in the left lateral orbitofrontal cortex, consistent with findings of previous volumetric studies on PTSD. But there were no significant correlations in the left lateral orbitofrontal cortex between Clinician‐Administered PTSD Scale scores and lGI. Conclusion: We suggest that abnormal gyrification in PTSD patients can be an important indicator of neurodevelopment deficits and may indeed be a biological marker for PTSD.